Potential of hydrogen production from sugarcane juice by Ethanoligenens harbinense Yuan-3. (10th November 2019) - Li, Weiming; Cheng, Chi; Cao, Guangli; Yang, Shang-Tian; Ren, Nanqi
Abstract: Inexpensive biomass is an ideal substrate for low-cost production of biohydrogen, but little was known about the biomass utilization performance of the ethanol-type hydrogen-producing bacteria Ethanoligenens harbinense . This study investigated the feasibility and performance of biohydrogen production by Ethanoligenens harbinense from sugarcane juice (SJ). Medium and process were firstly optimized with SJ as carbon source and the highest hydrogen yield was obtained when SJ was hydrolyzed by acid, and the medium contained 10 g/L sugar and 3 g/L yeast extract with pH at 6.0. Compared to batch fermentation, fed-batch fermentation with cell recycle showed significant improvement in hydrogen productivity and yield. The maximum productivity reached 5.22 mmol-H2 /Lh, 201.7% higher than that of the single batch (1.73 mmol-H2 /Lh). The highest H2 yield was 2.23 mol-H2 /mol-hexose, 65.2% higher than that of single batch fermentation. Cell immobilization with the fibrous bed bioreactor (FBB) also improved hydrogen productivity to 2.6 times that of batch fermentation with free cells. This study demonstrated the feasibility of hydrogen production from SJ with Ethanoligens sp., and a great improvement in hydrogen production was obtained by recycling cells and immobilizing cells in a fibrous bed bioreactor. Graphical abstract: Image 102655 Highlights: Sugarcane juice (SJ) was employed to produce H2 with E. harbinense. SJ medium and fermentation process were optimized for E. harbinense to produce H2 . Fed-batch fermentation gave 201.7% higher H2 productivity and 65.2% higher yield. Cell immobilization significantly improved H2 productivity by 1.6 times. Maximum H2 yield of 2.23 mol/mol-hexose was the best reported from SJ.